Pengaruh Permen Jahe dalam Mengatasi Keluhan Mual dan Muntah pada Ibu Hamil - Agnes Erna Taulina Purba; Sharfina Haslin; Ronni Naudur Siregar (Oksitosin : Jurnal Ilmiah Kebidanan, 2023)
Pregnancy is a natural process that causes physical and psychological changes due to hormonal changes. Often pregnancy enters a critical period if it is not passed comfortably by pregnant women. Pregnant women must be able to adapt psychologically and physiologically to pregnancy hormones. The effect of hormonal changes is nausea and vomiting in early pregnancy, especially in the morning. Nausea and vomiting can be reduced by using herbal ingredients. The method used in this study was a literature study on the benefits of ginger, then ginger was processed into ginger candies with added sugar and water. The ginger candy was then given to women who were pregnant for 4 days in the first trimester of pregnant women. Nausea and vomiting were measured before and after being given the ginger candy using the Pregnancy Unique Quantification of Emesis and Nausea (PUQE) instrument. The data were processed statistically to determine the effect of extra ginger candy on nausea and vomiting of pregnant women. After measuring the pretest and posttest giving ginger candy, it was concluded that there was an effect of ginger candy on reducing nausea and vomiting.